Penyuluhan Manfaat Jahe bagi Kesehatan Keluarga Guru dan Orang Tua KB-TK Santa Maria Juanda Jakarta Pusat - Rosita Stefani; Eko Fibryanto; Rahmi Amtha; Adrian Nova Fitri; Wiena Widyastuti; Miranti P Darmawanti; Faustine Katrini; Gisela Ellenia Vanessa; Vincentia Alice (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Oral health has an important influence in physical and mental health. Dental caries, the most common dental and oral disease, is related to dental plaque. Mouthwash can prevent the formation of plaque. Ginger, a plant that is easy to grow and found in Indonesia, can be an active ingredient in mouthwash. Ginger has many benefits in health such as antifungal, antimicrobial, anticancer, antidiabetic, antioxidant and anti-inflammatory. One of the methods to increase knowledge about role of ginger in oral health is to give counseling. This education shows that there is an increase in knowledge based on the results of the pretest and posttest, so that participants are expected to be able to apply the knowledge gained in daily life.